Effect of sintering holding time on low-temperature degradation of yttria stabilised zirconia ceramics - Sutharsini, U.; Ramesh, S.; Wong, Y.H.; Misran, H.; Yusuf, F.; Tan, C.Y.; Purbolaksono, J.; Teng, W.D. (Maney Publishing, 2014)
Effect of sintering holding time on low-temperature degradation of 3 mol-% yttria stabilised zirconia was investigated. Yttria stabilised zirconia samples were sintered using a two-step sintering cycle. The samples were initially heated to 1500°C with the heating rate of 10°C min−1, held for 1 minute before cooling down to 1200°C and kept at this temperature for varying holding times from 0 to 10 hours. The phase contents of the zirconia samples were measured using X-ray diffractometer, and the microstructural evaluation was evaluated by field emission scanning electron microscope. All the as-sintered samples exhibited 100% tetragonal phase and bulk density of about 6 g cm−3. The low-temperature degradation study was conducted under autoclave condition containing superheated steam at 180°C and 10 bar vapour pressure for periods up to 24 hours. The results showed that the tetragonal to monoclinic phase transformation decreased with increasing holding time up to 3 hours and thereafter it increased. The sample sintered with 3-hour holding time showed better aging resistance than other samples. It was found that the grain size of this sample was the lowest (0·29 μm) when compared to other samples.